Restoration of Historical Baths Within the Scope of Cultural Heritage and Their Use in Archaeological Tourism: Harput Hoca Hasan Bath - Özdemir, Ayşe (Taner NAMLI, 2025)
Architectural edifices such as mosques, caravanserais, Turkish baths, and tombs, which have survived to the present day and reflect the history and lifestyles of their respective regions, constitute a significant aspect of cultural heritage. The preservation and integration of these structures, which exhibit the characteristics of their construction periods, into tourism not only imprints them upon the visual memory of contemporary societies but also ensures their transmission to future generations. Maintaining the quality and authenticity of archaeological sites represents a crucial dimension of archaeotourism. This interdisciplinary field, at the intersection of archaeology and tourism, serves as a catalyst for local economic development and as a collaborative endeavor for sustainable cultural heritage management. Within the scope of cultural heritage, historical hamams have recently begun to be sustainably integrated into the socio-economic cycle of daily life through authentic restoration efforts. The Hoca Hasan Hamam, evaluated within this study, commenced cleaning, excavation, and restoration activities in 2021 and currently functions as a museum serving the community. The functionalization of this hamam structure as a museum, integrated into the city's socio-economic cycle, has been achieved through in-situ preservation during excavation works, the exhibition of recovered artifacts, and the support of the exhibition with ethnographic works.

Bulunduğu yörenin tarihini ve yaşam şekillerini yansıtan, günümüze kadar gelmiş cami, han, hamam, türbe, kervansaray gibi eserler kültürel miras olarak karşımıza çıkmaktadır. Yapıldıkları dönemin özelliklerini gösteren bu eserlerin korunması ve turizme kazandırılması, hem günümüz toplumlarının görsel hafızasına yerleşmesi, hem de gelecek nesillere aktarımını sağlamaktadır. Arkeolojik alanların kalitesini ve özgünlüğünü korumak, arkeoturizmin önemli bir yönüdür. Arkeoloji ve turizmin kesiştiği arkeoturizm, hem ekonomik olarak yerel kalkınmanın öncüsü hem de sürdürülebilir bir kültürel miras için disiplinlerarası bir çalışma olarak karşımıza çıkmaktadır. Kültürel miras kapsamında bulunan tarihi hamamlar da son dönemlerde aslına uygun restore edilerek günlük hayatın sosyo-ekonomik döngüsüne sürdürülebilir s?ekilde dahil edilmeye başlanmıştır. Çalışma kapsamında değerlendirilen Hoca Hasan Hamamı, 2021 yılında temizlik, kazı ve restorasyon çalışmalarına başlanan, günümüzde müze olarak topluma hizmet eden bir yapı olarak karşımıza çıkmaktadır. Şehrin sosyo-ekonomik döngüsüne dahil edilen hamam yapısı kazı çalışmaları sırasında yerinde korunma, bulunan eserlerin sergilenmesi ve etnografik eserlerle serginin desteklenmesi ile de müze olarak işlevselleştirilmiştir.
Kültürel Miras Kapsamında Tarihi Hamamların Restorasyonu ve Arkeoturizme Kazandırılması: Harput Hoca Hasan Hamamı
Keywords: Cultural and Natural Heritage; Kültürel ve Doğal Miras; Archaeology (Other); Arkeoloji (Diğer)